2019
DOI: 10.1182/blood-2019-126674
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion-Mediated Multiple Myeloma (MM) Disease Progression: Junctional Adhesion Molecule a Enhances Angiogenesis and Multiple Myeloma Dissemination and Predicts Poor Survival

Abstract: Multiple myeloma (MM) plasma cell (MMPC) interactions with the microenvironment control MMPC growth, survival, drug-resistance and intra- and extramedullary dissemination. Dissemination of MMPCs through bone marrow niches and in extra-medullary sites is an active process of invasion involving bone marrow endothelial cells, multiple adhesion molecules and chemokine receptors. Since enhanced angiogenesis characterizes MM, we investigated whether junctional adhesion molecule-A (JAM-A) mediated interactions betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Recently, we demonstrated that bone marrow endothelial cells from both newly diagnosed (NDMM) and relapsed-refractory multiple myeloma (RRMM) patients feed into a vicious cycle orchestrated by aberrant adhesion molecules on the bone marrow endothelial cells and plasma cell surface and correlate with poor clinical prognosis [ 31 , 35 , 88 ]. Based on this evidence and several pieces of data [ 89 , 90 ], increased adhesion molecules levels have been uncovered to contribute to more aggressive phenotype [ 29 , 91 ].…”
Section: Multiple Myeloma (Mm) As a Paradigm For Endothelial Gatekmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that bone marrow endothelial cells from both newly diagnosed (NDMM) and relapsed-refractory multiple myeloma (RRMM) patients feed into a vicious cycle orchestrated by aberrant adhesion molecules on the bone marrow endothelial cells and plasma cell surface and correlate with poor clinical prognosis [ 31 , 35 , 88 ]. Based on this evidence and several pieces of data [ 89 , 90 ], increased adhesion molecules levels have been uncovered to contribute to more aggressive phenotype [ 29 , 91 ].…”
Section: Multiple Myeloma (Mm) As a Paradigm For Endothelial Gatekmentioning
confidence: 99%
“…Consequently, using several pre-clinical models [ 30 , 88 , 102 ], blocking the adhesion system seems to halt blood vessel formation, reduce adhesion-mediated networks, and weaken neoplastic disease progression. These therapeutic effects of interfering with the adhesion system were observed in translational animal models, not in patients and, therefore, must be interpreted with caution.…”
Section: Multiple Myeloma (Mm) As a Paradigm For Endothelial Gatekmentioning
confidence: 99%
“…Lymphoproliferative disorders [ 89 , 90 ] and DLBCL [ 91 ] are no exception. Accordingly, strategies combining anti-angiogenic therapy and immunotherapy seem to have the potential to tip the balance of the tumor microenvironment and improve the treatment response of lymphoid malignancies [ 21 , 22 , 92 , 93 ]. These pieces of evidence prompted an intense translational investigation aimed at targeting angiogenesis and the immune system in a coordinated fashion, based on the preclinical insights available [ 94 , 95 ].…”
Section: Bridging the Gaps Between Disease Biology And Clinical Trmentioning
confidence: 99%
“…Additionally, in a mouse model, the use of an antiangiogenic anti-VEGFR-2 antibody in the early stage delayed tumor progression of MM; nonetheless, besides IMiDs, angiogenic-directed strategy did not show effective results in the unselected patient subgroup in patients with MM [130]. In order to achieve a patienttailored vasculogenic targeting, stringent patient stratification has been proposed by modulating from the critical step of MM evolution that can be critically dependent on vessel supply, such as smouldering phases [131] or extramedullary dissemination [132][133][134]. e next breakthrough of therapeutic strategy design is targeting the MM ecosystem together with the immune microenvironment.…”
Section: Targeting Angiogenesis and The Immunementioning
confidence: 99%